2023
DOI: 10.3989/loquens.2022.e086
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linguistic Comparison of the Pitch and Temporal Profiles between L1 and Chinese L2 Speakers of Spanish

Abstract: Cross-linguistic studies between intonational languages suggest that there is a universal trend during the L2 learning process regarding pitch and temporal characteristics. We extend these hypotheses to Chinese learners of Peninsular Spanish-a new pairing of tone and non-tone languages. Using six pitch and temporal metrics, we examine how Chinese learners’ pitch and temporal profiles deviated from those of L1 native speakers and explore the factors that may contribute to L2 speech deviations. The Discourse Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The significance test of the first GLM revealed that Mandarin learners' accuracy in perceiving sentences with two stressed words was significantly influenced by the interaction between sentence modality and gate [χ 2 (3) = 24.25, p < .0001], L2 proficiency [χ 2 (2) = 14.09, p < .001], pragmatic skill [χ 2 (1) = 31.19, p < .0001)], and musical ability [χ 2 (1) = 6.04, p < .05]. However, stress position, age, and gender did not significantly impact auditory evaluation of L2 sentences.…”
Section: Results For Sentences With Two Stressed Wordsmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance test of the first GLM revealed that Mandarin learners' accuracy in perceiving sentences with two stressed words was significantly influenced by the interaction between sentence modality and gate [χ 2 (3) = 24.25, p < .0001], L2 proficiency [χ 2 (2) = 14.09, p < .001], pragmatic skill [χ 2 (1) = 31.19, p < .0001)], and musical ability [χ 2 (1) = 6.04, p < .05]. However, stress position, age, and gender did not significantly impact auditory evaluation of L2 sentences.…”
Section: Results For Sentences With Two Stressed Wordsmentioning
confidence: 99%
“…The significance test of the second GLM indicated that the L2 perception of Spanish sentences with one stressed word was significantly impacted by sentence modality [χ 2 (1) = 52.60, p < .0001], gate [χ 2 (1) = 70.39, p < .0001], stress pattern [χ 2 (1) = 4.77, p < .05], pragmatic skill [χ 2 (1) = 15.33, p < .0001], and musical ability [χ 2 (1) = 4.36, p < .05]. However, L2 proficiency, age, and gender did not significantly influence one-word sentence perception (all ps > .1).…”
Section: Results For Sentences With One Stressed Wordmentioning
confidence: 99%
See 1 more Smart Citation